LEVERAGING PUBLIC-PRIVATE PARTNERSHIPS: STRATEGIES FOR OPTIMAL INVESTMENT FINANCING - Yakubova, Samira (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
Public-private partnerships (PPPs) have emerged as a pivotal mechanism for financing investment activities across the globe. By leveraging the strengths of both the public and private sectors, PPPs offer a unique solution to address infrastructural and developmental challenges. This article delves into the intricacies of PPPs, their historical context, benefits, challenges, and provides recommendations for their effective implementation in Uzbekistan.